Pengalaman Pasien yang Pertama Kali Akan Menjalani Operasi di RSUD dr. R. Goeteng Taroenadibrata Purbalingga - Putri, Tisya Noor Qomara; Firdaus, Eza Kemal; Yanti, Linda (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The primary research issue explored in this thesis is the psychological and emotional challenges faced by patients undergoing surgery for the first time. These challenges include anxiety, fear, and concerns regarding the surgical procedure, potential pain, and the overall experience in the operating room. The objective of this study is to understand the experiences of first-time surgery patients and identify the factors influencing their preoperative psychological state. This research adopts a qualitative methodology with a phenomenological approach, aiming to delve into the personal experiences and perceptions of individuals related to a specific phenomenon—in this case, the patients’ preoperative experience. This approach involves collecting descriptive data through interviews and observations to gain a deep insight into participants’ lived experiences. The study reveals that preoperative preparedness is shaped by several key factors. Mental preparation is crucial in reducing anxiety and fostering cooperation during surgery. Physiological preparation ensures the patient’s physical readiness. Psychological preparation, including health education, helps alleviate stress for both the patient and their family, minimizes the risk of postoperative complications, and improves overall outcomes. The research concludes that preoperative experiences are largely influenced by emotional factors such as anxiety and curiosity. Additionally, family support plays a critical role in the patient’s recovery. The study recommends enhancing psychological preparation through health education to reduce stress and improve outcomes, emphasizing the significance of involving the family in decision-making and providing support throughout the process.